OBITUARY PRESENTED IN INDONESIAN NEWSPAPER - Atiqa Sabardila; Adyana Sunanda; Yunus Sulistyono; Dini Restiyanti Pratiwi; Agus Budi Wahyudi (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2020)
The newspaper enables the readers to obtain enlightenment, particularly moral values. Moral values can be obtained through obituary writings. This study was aimed at elaborating the reference, author’s perspective, technique of collecting material, role assertion, contribution to writing biography, and motive in the obituary. The data were obtained through a documentation technique while the data source was attained from the printed version of the called Kompas Indonesia newspapers from 2015 to 2017. The newspaper was the only one in the country giving this special rubric. The study applied the referential identity method, marker reading technique, and pragmatic identity analysis as well as pedagogic and hermeneutic approach. Results show that the obituary texts in the newspaper are potential to become a learning material in Indonesian language education, particularly in the elementary school. The inspirational figures can further impact on students’ character building. Keywords: obituary, character building, motives, reference, Kompas PEMBERITAAN OBITUARI DALAM SURAT KABAR INDONESIA AbstrakSurat kabar memungkinkan pembaca mendapatkan pencerahan, khususnya nilai-nilai moral. Nilai-nilai moral dapat diperoleh melalui penulisan berita kematian di surat kabar. Penelitian ini bertujuan untuk menguraikan referensi, perspektif penulis, teknik mengumpulkan bahan, peran peran, kontribusi untuk menulis biografi, dan motif dalam berita kematian. Data diperoleh melalui teknik dokumentasi; sementara sumber data diperoleh dari surat kabar cetak bernama Kompas Indonesia pada 2015-2017. Sumber data hanya diambil dari koran Kompas mengingat bahwa Kompas satu-satunya koran yang menyediakan kolom mengenai isu ini. Penelitian ini menggunakan metode identitas referensial dan teknik marker reading. Analisis data dilakukan dengan menggunakan metode referensial, teknik membaca penanda, dan metode identitas pragmatis serta pendekatan pedagogik dan hermeneutik. Berdasarkan analisis data yang disajikan dalam artikel ini, teks berita kematian berpotensi menjadi bahan pembelajaran dalam pendidikan bahasa Indonesia, khususnya di Sekolah Dasar. Tokoh-tokoh inspirasional dapat lebih jauh berdampak pada pembentukan karakter siswa. Kata kunci: obituari, pembentukan karakter, motif, referensi, Kompas